2021
DOI: 10.32598/ptj.11.2.429.2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Lower Limb Flexibility With Motor Function and Risk of Falling in Visually Impaired Individuals

Abstract: Objective: The present study aimed to investigate the flexibility of the ankle and knee joints and to determine its relationship with balance, motor function, and risk of falling in visually impaired individuals. Methods: The sample consisted of 32 blind males, 20-30 years old. They were selected by the purposeful sampling method. We used modified stork tests, tendon gait, and Berg balance scale to evaluate their balance. The Tinetti test was used to evaluate motor performance and the Timed Up and Go (TUG) tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Hence, when standing and walking, compensatory movements are not created by the auxiliary muscle and thus improving balance. Various studies have also shown that limitations in the range of motion of the ankle, knee, and thigh reduce balance [45].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, when standing and walking, compensatory movements are not created by the auxiliary muscle and thus improving balance. Various studies have also shown that limitations in the range of motion of the ankle, knee, and thigh reduce balance [45].…”
Section: Discussionmentioning
confidence: 99%
“…This may depend on the specific difficulty separating head and trunk movements, especially during rotation around the vertical axis, as well as disability-related upper body tension and stiffness [ 14 , 15 ]. As a result, these individuals often deal with movement limitations both in daily life and leisure/sport activities and, if this motor experience lack is not intentionally compensated, it can easily lead to sedentary life-related physical and mental disorders [ 16 , 17 ]. Spatial awareness and management are generally accomplished via integration of visual, vestibular, and proprioceptive cues [ 18 , 19 , 20 ], but in case of visual impairment, subjects strongly rely on egocentric references and acoustic feedback [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%